Rancang Bangun Aplikasi Marketplace Stikom Surabaya Berbasis Android - Maulana, Nanda Rizka; Hariadi, Bambang; Amelia, Tan (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2020)
Currently Stikom Surabaya has a marketplace in the form of a web that can accommodate the work of students and lecturers, this web marketplace already has the main features needed to be able to carry out buying and selling transactions. This type of Surabaya Stikom marketplace is global, a marketplace that sells various types of products that have no connection with other products. Based on the explanation above, it can be seen that the problem that occurs is that a platform is needed that can expand the market share of the Marketplace Surabaya Stikom and make it easier for users to access the Marketplace Surabaya Stikom. Statistical data The global Operation System (OS) market share from 2009-2018 concluded that by the second quarter of 2018 as much as 88% of the global OS market share was dominated by Android while 11.9% was IOS and the remaining 0.1% was the other OS. So that the new platform developed for the Marketplace Surabaya Stikom will use the Android Operation System. Based on the existing problems, research will be conducted to design and build an application for the Android-based Marketplace Stikom Surabaya. The conclusion that can be drawn based on the results of the implementation and evaluation of making an Android-based Surabaya Marketplace Stikom application is to produce an application that can be used as a container for making sales and purchase transactions. This application can also help sellers and buyers to monitor and process ongoing transactions.